Green Miniaturized Extraction and Microextraction of Polycyclic Aromatic Hydrocarbons from Foods and Beverages - Manousi, Natalia; Zachariadis, George A. (Current Analytical Chemistry, 2021)
Background: Polycyclic aromatic hydrocarbons (PAHs) are common environmental contaminants consisting of two or more fused benzene rings. PAHs can be introduced into foodstuffs through different ways, such as smoking, roasting and grilling for meat and fish, absorption from the environment for edible oils, chemical treatment of crops for plant-based products, or contamination through packaging during storage. Due to the low concentrations of PAHs in foodstuffs, a clean-up and preconcentration sample preparation technique is of high importance. Until recently, solid-phase and liquid-liquid extraction were the most popular sample preparation techniques for the extraction of PAHs from food matrices. However, due to the fundamental drawbacks of those extraction procedures, a plethora of novel methods, including micro-extraction techniques and miniaturized extraction techniques, have been developed. Moreover, a wide variety of novel adsorbent materials (e.g., metal-organic frameworks, carbon-based materials, etc.) have been synthesized and applied for PAHs’ extraction. Objective: This review aims to discuss recent advances in the extraction techniques of PAHs from food samples, utilizing novel sample preparation approaches and adsorbents. Conclusion: Compared with the traditional sample preparation techniques, the herein discussed green miniaturized extraction and microextraction techniques offer multiple benefits, including simplicity, reduced sample preparation time, as well as reduced consumption of organic solvents.
Keywords: microextraction